Assessment of Business Process Maturity Model in Culinary SMEs as a Pre-Stage of Enterprise Resource Planning Implementation - Prakoso, Nur Abdillah Bagus; Setiawan, Danang; Rachmad, Azzahra Tiffany; Azzahra, Berliana Frisca (TALENTA Publisher, 2023)
The SMEs sector is predicted to have a surplus of ERP implementation projects in 2024, with 60% of the total implementation projects. However, the ERP implementation growth cannot be separated from the threat of project failure (35%) and project delays (55%). This study measured the maturity of business processes as a pre-implementation stage to reduce the risk of ERP implementation failure. The object studied was three culinary SMEs in Yogyakarta. This paper used McCormack’s theory of business process management maturity model, combined with the ICT maturity model developed by Pham. The assessment showed that the three SMEs were at the lowest level of business process maturity, the ad hoc level. Meanwhile, the ICT maturity varies from inactive to substantial. However, SME A had the eligibility to implement an ERP system but first needed to perform the business process re-engineering. The recommendations were designed for SME A to enhance its business process flow by proposing a business process based on the best practice process used by ERP system providers.